2020
DOI: 10.11646/zootaxa.4859.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Five new species of Phalangopsis Serville, 1831 (Orthoptera: Phalangopsidae) from Brazilian caves in the Amazon Forest

Abstract: The current work presents the description of five new cricket species for the genus Phalangopsis Serville, 1831 found in Brazilian caves in the Amazonas, Mato Grosso and Pará states, northern Brazil. The morphology of the phallic complex was used as the main criterion for distinguishing the species. In addition, we present data on the natural history and ecology of the new species as well as hypothesis about the variations of tegmina size in relation to the subterranean lifestyle for the genus. Finally, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 881 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In particular, many South American cave phalangopsidae (e.g. Adelosgryllus, Endecous, Phalangopsis and Strinatia) (Campos et al 2017, Castro-Souza et al 2020b, Cigliano et al 2022, Junta et al 2020, Merlo et al 2022, Mesa et al 1999) reveal pre-adaptations reported for other cave crickets (Desutter-Grandcolas 1993;Desutter-Grandcolas 1997;Heads 2010), such as eye size reduced, loss of ocelli, absence of auditory tympana and body discoloration. However, to confirm that the traits are pre-adaptations, it is necessary to evaluate them together with the habitat from a phylogenetic perspective (Desutter-Grandcolas 1997).…”
Section: Caves As Potential Refuges For the Species Conservation In T...mentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, many South American cave phalangopsidae (e.g. Adelosgryllus, Endecous, Phalangopsis and Strinatia) (Campos et al 2017, Castro-Souza et al 2020b, Cigliano et al 2022, Junta et al 2020, Merlo et al 2022, Mesa et al 1999) reveal pre-adaptations reported for other cave crickets (Desutter-Grandcolas 1993;Desutter-Grandcolas 1997;Heads 2010), such as eye size reduced, loss of ocelli, absence of auditory tympana and body discoloration. However, to confirm that the traits are pre-adaptations, it is necessary to evaluate them together with the habitat from a phylogenetic perspective (Desutter-Grandcolas 1997).…”
Section: Caves As Potential Refuges For the Species Conservation In T...mentioning
confidence: 96%
“…The future predictions (2080-2100) showed that the potential distribution of Endecous crickets would become restricted on epigean habitats, with its potential isolation in caves in South America, corroborating our second hypothesis. This habitat reduction or restriction can be intensified because favourable epigean habitats, such as the Cerrado and Atlantic Rainforests, have been strongly threatened by agricultural expansion, urbanization and mining (Dinerstein et al 2017, MapBiomas Project 2021, Mittermeier et al 2004, Myers et al 2000, Souza et al 2020, Sugai et al 2015.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...mentioning
confidence: 99%
“…These caves are small, with their sizes varying around 30 meters to 200 meters, connected to a huge network of small channels (= canaliculi, typically found in the Canga formation), which considerably increases the habitats for cave-dwelling species. The Carajás region is also the shelter of several troglobitic and troglophilic species such as spiders, beetles, centipedes, crickets, and other invertebrates (Pinto-da-Rocha 1995;Ázara & Ferreira 2014;Parizotto et al 2017;Chagas-Jr & Bichuette 2018;Rodrigues et al 2018;Bouzan et al 2019a;Oliveira et al 2019;Junta et al 2020). Mauriès, 1974 Figs 29D-E, 129-130, 164K, 166L, 173A, 179A, 188; Pseudonannolene strinatii - Mauriès & Geoffroy 2000: 155.…”
Section: Distributionmentioning
confidence: 99%
“…To date, the economy of the Serra dos Carajás region has been intensified due to mining operations in its huge deposits of iron ore, influencing directly the local urban development and environmental pressures on land use (Palheta et al 2017). The rock outcrops of this region harbor numerous endemic invertebrates (Chagas-Jr & Bichuette 2018; Brescovit et al 2018; Asenjo et al 2019; Campos-Filho et al 2020; Junta et al 2020; Teodoro et al 2021), including some millipede species such as Glomeridesmus spelaeus Iniesta & Wesener, 2012 (Glomeridesmida Latzel, 1884, Glomeridesmidae Latzel, 1884), Pseudonannolene spelaea Iniesta & Ferreira, 2013 (Spirostreptida Brandt, 1833, Pseudonannolenidae Silvestri, 1895), Parastenonia carajas Bouzan & Iniesta, 2019 (Polydesmida Leach, 1815, Chelodesmidae Cook, 1895), and Stemmiulus brasiliensis Iniesta & Ferreira, 2015 (Stemmiulida Pocock, 1894, Stemmiulidae Pocock, 1894) (Iniesta et al 2012; Iniesta & Ferreira 2013, 2015; Bouzan et al 2019).…”
Section: Introductionmentioning
confidence: 99%